Essentials of sociology - Brinkerhoff, David B.; Weitz, Rose; Ortega, Suzanne Trager (Wadsworth Cengage Learning, 2014)
This title shows students the interrelatedness of core concepts and their applications in real-world scenarios. It provides research coverage of the standard introductory topics in a balanced and unbiased manner in just 15 concise chapters.